The Effectiveness of Radial Extracorporeal Shock Wave Therapy for Chronic Achilles Tendinopathy: A Case Report with 18 Months Follow-Up - Erieta Nikolikj Dimitrova; Cvetanka Gjerakaroska-Savevska; Valentina Koevska; Biljana Mitrevska; Marija Gocevska; Maja Manoleva; Biljana Kalchovska Ivanovska (ID Design 2012/Scienfitic Foundation SPIROSKI, 2018)
Achilles tendinopathy (AT) is a pathological state resulting from repetitive loading or stress on the tendon. The article aims to evaluate the effects of the low - energy radial extracorporeal shockwave therapy (RESWT) in the treatment of the adult with chronic insertional Achilles tendinopathy (AT) after the unsuccessful conservative treatment, with 18 months follow - up evaluation.